2011
DOI: 10.1007/s12291-011-0140-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Endothelial Dysfunction in Health and Disease; Using Various Parameters

Abstract: Conditions like hypertension, atherosclerosis and diabetes are known to be the result of endothelial dysfunction which could begin early in the life of an individual. The markers of endothelial dysfunction studied in the present work are plasma hemoglobin, serum high sensitivity C-reactive protein (hsCRP) and plasma nitrite and nitrate. We studied the onset of endothelial dysfunction with increase in age as well as in disease condition like newly detected hypertensives and of hypertensive diabetic patients. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…11 In the current study there was a significant correlation between CCAIMT and TC, TG, LDL, VLDL (p< 0.001 for all). It was also seen that CCAIMT increased with increase in the TC, TG, LDL, VLDL levels 12 The current study also observed a significant negative correlation between CCAIMT and HDL levels (p <0.001). It was also observed that CCAIMT was inversely proportional to HDL levels with correlation coefficient r= -0.730.…”
Section: Resultssupporting
confidence: 80%
“…11 In the current study there was a significant correlation between CCAIMT and TC, TG, LDL, VLDL (p< 0.001 for all). It was also seen that CCAIMT increased with increase in the TC, TG, LDL, VLDL levels 12 The current study also observed a significant negative correlation between CCAIMT and HDL levels (p <0.001). It was also observed that CCAIMT was inversely proportional to HDL levels with correlation coefficient r= -0.730.…”
Section: Resultssupporting
confidence: 80%
“…Also, while uric acid levels in serum were not affected by the high fructose intake the high glucose diet led to a significant decrease. However, while systolic and diastolic blood pressure also remained unaffected by the different diets (Table 4), plasma NOx levels shown to be indicative of vascular endothelial dysfunction [15] were significantly lower after subjects had consumed the fructose-enriched diet for 3 days (-47%). A similar drop in NOx levels was not found after subjects had eaten the glucose-enriched diet (see Figure 2).…”
Section: Effect Of a Fructose-and Glucose-enriched Diet Respectivelymentioning
confidence: 99%
“…Forty patients were included in this study. The median hs-CRP, NO, and systolic BP (SBP) of the patients were 6.55 mg/dL (0.50-43.5), 27.77 mg/dL (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), respectively. The correlation analysis showed that there was a strong significant negative correlation between hs-CRP levels and NO (r = −0.680, p = 0.000).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Jalali et al reported in a study of 179 patients with stage 5 ESRD on HD, it was found that an increase in hs-CRP was associated with endothelial dysfunction. hs-CRP levels also increase with age and worsening of the disease, which can lead to an increase in BP (p < 0.001) [23]. Some acute phase reactants such as CRP and ferritin are markers of inflammatory reactions caused by the stimulation of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%